Pengolahan Bahan Pustaka di Perpustakaan SMAN 1 Kabupaten Pesisir Selatan - Jajulita, Mulyatri; Rahmah, Elva (Ilmu Informasi Perpustakaan dan Kearsipan, 2015)
This article aims to describe: (1) how the processing of library materials in the Library of SMAN 1 Painan South Coastal District, (2) what are the obstacles encountered in the processing of library materials in the Library of SMA N 1 Painan South Coastal District and (3) how problem solving encountered in the processing of library materials in the Library of SMAN 1 Painan South Coastal District. Data were collected through observation and interviews with librarians SMAN 1 Painan South Coastal District. Analyzing data descriptively. By analyzing the data, it was concluded matters as follows. First, the processing of library materials in the library SMAN 1 South Coastal District has not run with the maximum, because not all the implementation of activities such as, inventory of library materials, library materials classification, cataloging library materials, and the completion of the completeness of library materials. Second, the constraints encountered in the processing of library materials, namely: (1) is not maximal performance librarian, (2) lack of funds or the budgets allocated to libraries, (3) facilities and infrastructure are inadequate. Third, efforts were made so that the processing of library materials in the library SMAN 1 Painan South Coastal District goes well, namely: (1) improve the performance of librarians, (2) provide funding / budget for the library, (3) complement and provide facilities and infrastructure adequate. Keywords: management; library materials